Unpleasant but effective: Newspaper coverage of cancer screening and cancer in the Netherlands from 2010 to 2022 - Martin-Pieter Jansen; Inge Stortenbeker; Hanneke Hendriks; Suzan Verberne; Gert-Jan de Bruijn; Enny Das (PLoS ONE, 2025)
Participation rates in cancer screening programs (CSPs) have shown a declining trend, and research suggests that news media reports may contribute to public opinion. Therefore, we aimed to understand how Dutch news media report on CSPs. We mainly focused on breast, colorectal, and cervical CSPs but did not exclude reports on other cancer types. Through a systematic content analysis 5,503 news articles from 2010 to 2022 were analyzed for key characteristics such as topic and reported cancer type. Results showed that most news reports framed CSPs as effective and beneficial for public health. The reliability of screening methods was sometimes criticized. In these cases, reports discussed overdiagnosis or medicalization. Although reports were positive about CSPs’ effectiveness, they were sometimes negative about organizational, psychological, and physiological aspects. Early detection and diagnosis of cancer are portrayed as having benefits that outweigh the costs. These findings show that news media often describe CSPs as a ‘necessary evil’ and that participation may be inconvenient and stressful, but that early detection and diagnosis of cancer are benefits that seem to outweigh this necessary evil.